Localization of SARS-CoV-2 Capping Enzymes Revealed by an Antibody against the nsp10 Subunit - Horova, Vladimira; Landova, Barbora; Hodek, Jan; Chalupsky, Karel; Krafcikova, Petra; Chalupska, Dominika; Duchoslav, Vojtech; Weber, Jan; Boura, Evzen; Klima, Martin (Viruses, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the coronavirus disease-19 pandemic. One of the key components of the coronavirus replication complex are the RNA methyltransferases (MTases), RNA-modifying enzymes crucial for RNA cap formation. Recently, the structure of the 2'-O MTase has become available; however, its biological characterization within the infected cells remains largely elusive. Here, we report a novel monoclonal antibody directed against the SARS-CoV-2 non-structural protein nsp10, a subunit of both the 2'-O RNA and N7 MTase protein complexes. Using this antibody, we investigated the subcellular localization of the SARS-CoV-2 MTases in cells infected with the SARS-CoV-2.
Keywords: coronavirus; methyltransferase; SARS-CoV-2; methyltransferasy; nsp16; Viral Regulatory and Accessory Proteins; RNA Caps; capping enzyme; RNA, Viral; virové nestrukturální proteiny; Antibodies, Monoclonal; Viral Nonstructural Proteins; lidé; Protein Transport; nsp14; Methyltransferases; COVID-19; RNA virová; transport proteinů; virové regulační a přídatné proteiny; monoklonální protilátky; RNA čepičky; nsp10; Humans